Us : getting past you & me to build a more loving relationship - Real, Terrence (Goop Press/Rodale, 2022)
"You've probably heard some variation of the idea that before you can love someone else, you first have to learn to love yourself. Renowned family therapist and marriage counselor and bestselling author Terrence Real says that we've got it all wrong. In fact, the way to save your relationship is not by working on yourself, but instead by working together. Continuing to focus on yourself will just feed the problem, which is that most of us developed a set of techniques to survive our families that no longer serve us as adults. You can learn to tap into your wiser, more collaborative self. In this groundbreaking book, Real offers a new set of science-backed relational skills that have saved real marriages on the brink. Using psychology, history, and stories of actual couples who have entered his office, Real helps readers move beyond their traumas and stressors and shift from thinking in terms of me and you to a different consciousness. The consciousness of us. The Hail Mary family therapist for couples on the verge of divorce, Real teaches us how to speak up for ourselves with love and build solid, loving relationships that are authentic and interdependent"--